Global social work : crossing borders, blurring boundaries - Noble, Carolyn; Strauss, Helle; Littlechild, Brian, 1953- (Sydney University Press, 2014)
Global Social Work: Crossing Borders, Blurring Boundaries provides a reference point for moving the current social work discourse towards understanding the local and global context in its broader significance.